Flexible Building Blocks for Software Defined Network Function Virtualization - TaheriMonfared, Aryan; Rong, Chunming (EAI Endorsed Transactions on Cloud Systems, 2014)
Current virtual networks offered by IaaS cloud providers are not under complete control of their tenants. The virtual network configuration is carried out by the service provider, and the functionality is limited by the provider’s offerings. This paper presents a new approach for building and maintaining tenant-programmable virtual networks. This type of virtual networks are the basic building blocks for network function virtualization, and significantly facilitates the implementation of network functions in software. Our approach gives tenants complete control over provisioned virtual network components, and simplifies the integration with on-premises resources. The implementation confirmed the practicality and scalability of the solution, at the cost of a small overhead.